Health-related quality of life and everyday functioning in the flood-affected population in Germany: a case study of the 2021 floods in West Germany - Sairam, Nivedita; Buch, Anna; Zenker, Marie-Luise; Dillenardt, Lisa; Coenen, Michaela; Thieken, Annegret; Jung-Sievers, Caroline (GeoHealth, 2025)
Floods lead to adverse impacts not only in financial terms but also on the health of the exposed population. We report on health-related Quality of Life (QoL) and functioning in the population affected by the 2021 flooding in Germany using an empirical survey data set. Health-related QoL and functioning are represented by two scores-(a) The EuroQoL 5D Visual Analog Scale (EQ-5D VAS) and (b) The 12-Item World Health Organization Disability Assessment Schedule (WHODAS 2.0), respectively. By applying an incremental linear regression model and Machine Learning models, we infer that health-related QoL and functioning are strongly negatively related to the psychological burden from those being affected by the flooding. This includes how often they think about the traumatic event. Home owners were found to have worse QoL and functioning than tenants. Household income and the status of repair/reconstruction of flood damages—in specific, insurance benefits, private donation and satisfactory claims compensation are associated with high health-related QoL and functioning. These findings highlight the importance of strengthening the health-related QoL of flood affected populations and emphasizes the strong association between recovery and health-related QoL and functioning of flood-affected populations.